KINERJA PETUGAS PELAKSANA DALAM PELAYANAN PROGRAM MANAJEMEN TERPADU BALITA SAKIT (MTBS)DI KABUPATEN BANYUMAS - Sugi Purwanti; Atik Mawarni; Martha Irene K (Jurnal Ilmiah Kesehatan Keperawatan, 2012)
Integrated Management of Childhood Illness (IMCI) has been implemented in Banyumas Regency as a part of efforts to lower infant mortality and under five children Death. But in 2007, under-five mortality is still high at 9.6 / 1,000 live births. A preliminary study conducted in the three health centers shows that not all infants got good care IMCI well. This is due to the existence of several sub-optimal care by IMCI officer. The purpose of research is to describe the performance of health workers in implementing IMCI consisting of quality, quantity, cost effectiveness, supervision requirements and timeliness in service IMCI in Banyumas. This is an observation research consisting of 99 samples of IMCI officers. The Research instrument is a quesionar that the validity and reliability have been tested. The data analysis technique is frequency distribution that used to obtain description of the research variables.  The results show that not all officers carried SOP of IMCI (6% to 17%). Officers did not provide IMCI services to all under five children who came clinic (37.4%). Medical history records of the under five patient were not recorded separately. Supervision by the leaders did not involve the IMCI officers in finding altrenatif problem solving. Not all health centers submitted reports on time. It is suggested to do a more intensive socialization to all officers regarding issues related to IMCI program. Keywords: Performance of IMCI officer, IMCI